The Team Games Tournament Model Enhances Engagement and Interest in Learning Among Class VIII Students - Safitri, Lale Aprihatin Diana; Fathurrahman, Fathurrahman (AS-SABIQUN, 2024)
This study examines the effectiveness of the Team Games Tournament (TGT) model in enhancing student engagement and interest in learning among eighth-grade students at SMP Islam Terampil NM NW Pancor Kopong. The research employs a classroom action research design, consisting of pre-cycle, cycle I, and cycle II. Data were collected through observations, questionnaires, and tests, focusing on students' learning interest and activity levels. The results indicate a significant improvement in both engagement and interest across the cycles. In the pre-cycle phase, only 5 students exhibited high engagement, while 9 and 11 students demonstrated medium and low engagement, respectively. By cycle I, these figures rose to 8 high, 10 medium, and 4 low engagement students. Cycle II further revealed a notable increase, with 14 students showing high engagement and 8 at a medium level. The distribution frequency analysis highlighted that the average score for learning interest was 2.12, with the highest mean recorded in group participation and games (2.54). Additionally, statistical analysis through paired t-tests revealed significant differences (p < 0.001) in both learning interest and engagement. This underscores the positive impact of TGT in fostering an interactive and motivating learning environment. Although the findings suggest meaningful advancements, the study acknowledges limitations and encourages further research to refine and expand upon the results. This study contributes to the literature on effective teaching strategies in enhancing student motivation and participation in educational settings.